LATE NEOGENE SEISMIC STRUCTURES OF THE SOUTH BATANTA BASIN, WEST PAPUA - Dida Kusnida; Tommy Naibaho (BULLETIN OF THE MARINE GEOLOGY, 2014)
Study on multi-channel seismic records from South Batanta Basin, West Papua acquired during RV Geomarin III cruise in 2013 were aimed to invent and map geological aspects and for geo-tectonic and geological history studies. Seismic data indicate that sediment sequences which can be observed from our seismic system in the study area are characterized by pre-extension sediments (Lower Early Miocene-Upper Early Pliocene), syn-extension sediments (Lower Middle Pliocene-Upper Late Pliocene), post-extension sediments (Early Pleistocene), and syn-inversion sediments (Late Pleistocene-Recent) typical of the West Papua tectonic system. In the study area, sediment sequences are possibly characterized by clastical sedimentary cover such as slumps, debrites and turbidites. Key words: South Batanta Basin, seismic sequence, tectonic, faults, clastical sediments. Studi rekaman seismik multi kanal dari Cekungan Batanta Selatan, Papua Barat yang diperoleh selama pelayaran KR Geomarin III pada tahun 2013 bertujuan untuk menginventarisir dan memetakan aspek-aspek geologi serta untuk studi geo-tektonik dan sejarah geologi. Data seismik menunjukkan bahwa urutan sedimen yang dapat diamati dari sistem seismik di daerah studi ditandai oleh sedimen pra-ekstensi (Miosen Awal Bagian Bawah-Pliosen Awal Bagian Atas), sedimen syn-ekstensi (Pliosen Tengah Bagian Bawah-Pliosen Akhir Bagian Atas), sedimen post-ekstensi (Plestosen Awal), dan sedimen syn-inversi (Pleistosen Akhir-Resen) tipikal sistem tektonik Papua Barat. Di daerah studi, urutan sedimen dicirikan oleh sedimen penutup klastika kemungkinan berupa slump, debrit dan turbidit. Kata kunci: Cekungan Batanta Selatan, sekuen seismik, tektonik, sesar, sedimen klastika.